Study the Relationship of Genetic Polymorphism of Transfferin Gene with Productive Performance in Holstein Cows for Selection - Hussein, Jaafer Ramadhan; AL-Anbari, N. N. (Journal of Kerbala for Agricultural Sciences, 2016)
This study is conducted in Dairy Cattle Farm and the Physiology Laboratory, College of Agriculture, Department of Animals Resources, Abu-Ghraib and also in a Laboratory dealing with the analysis of molecular genetic for the period 1/11/2013 to 7/11/2014. The objective to this study is to identify the genotypes for transferrin gene (Tf) and the relationship among these genotypes with some growth and production of 54 Holstein cows and 39 progeny. The percentage of genotype distribution for the transferring gene in sample of studied cows is 25.93 , 55.55 and 18.52 % for the genotypes TT, TC and CC respectively and the differences between these percentages are highly significant and the effect of the genotypes of the transferrin gene on the total milk production and the lactation period is significant (P<0.05) while the cows with TC genotype give the highest total milk production (2149.03 ± 295.05 kg/season) with a lactation period of 170.92 ± 18.59 days. The results of the current also study show that the components of the studied milk (fat, lactose, non-fatty soluble solids) are influenced significantly (P<0.05) by the differences between the genotype of the transferrin gene, while the percentage of the protein and ash in the milk is not influenced by the genotype. The body weight at birth is significantly influenced by the genotypes of the transferring gene and alleles frequencies for alleles (T) is 0.54 while the alleles frequencies for alleles (C) is 0.46 according to the analysis of transferrin gene (Tf) in this study. The application of this study in bigger samples of animals for many productivity seasons may be gave more accurate results for applying replacement and culling strategies.